2010
DOI: 10.1001/archinternmed.2010.32
|View full text |Cite
|
Sign up to set email alerts
|

Curbing Methicillin-Resistant Staphylococcus aureus in 38 French Hospitals Through a 15-Year Institutional Control Program

Abstract: A sustained reduction of MRSA burden can be obtained at the scale of a large hospital institution with high endemic MRSA rates, providing that an intensive program is maintained for a long period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(73 citation statements)
references
References 44 publications
6
61
1
4
Order By: Relevance
“…In each hospital, a local infection control team (LICT) is in charge of prevention and surveillance of healthcare-associated infections, but decisions of foremost importance for the whole institution, e.g. multidrug resistance control programme, are coordinated by a multidisciplinary central infection control team (CICT), including one infectious disease physician, one bacteriologist, one epidemiologist and one nurse [7].…”
Section: Methods Settingmentioning
confidence: 99%
“…In each hospital, a local infection control team (LICT) is in charge of prevention and surveillance of healthcare-associated infections, but decisions of foremost importance for the whole institution, e.g. multidrug resistance control programme, are coordinated by a multidisciplinary central infection control team (CICT), including one infectious disease physician, one bacteriologist, one epidemiologist and one nurse [7].…”
Section: Methods Settingmentioning
confidence: 99%
“…1). [13][14][15][16] Although this reduction was attributed to improved infection control practices in the West, the decline was also noted from the developing countries where infection control remains to be an unsolved problem, although the figures reported from these countries may be less reliable. 12 The most recent data available from ECDC in 2013 indicate that in Europe, Romania has the highest rates of MRSA (>50%) isolated from cerebrospinal fluid (CSF) or blood and additional 5 countries in the EU region (Cyprus, Greece, Hungary, Italy and Spain) have rates between 25% and 50%.…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
“…Jarlier et al reported a concerted campaign in France, starting in 1993, based primarily on guidelines, barrier precautions and isolation. 22 Improvement over subsequent years was modest, but increased following a central ministerial initiative in 2001 that implemented five reportable national quality indicators to benchmark hospital performance. 23 Improvement was sharpest in intensive care units and less rapid in general wards, especially in medical departments where the reduction before 2001 was negligible.…”
Section: Boxmentioning
confidence: 99%
“…23 Improvement was sharpest in intensive care units and less rapid in general wards, especially in medical departments where the reduction before 2001 was negligible. 22 Malta and Italy have also reported significant improvement in MRSA incidence in intensive care that was not evident in general wards. In high UAI backgrounds, change may be more difficult to implement in the heterogeneous environments found in general wards as opposed to intensive care environments, where nurses are normally assigned to individual patients and may feel a greater personal ownership for the outcome.…”
Section: Boxmentioning
confidence: 99%